Handbook of LGBT Elders - Harley, Debra A.; Teaster, Pamela B. (Springer, 2016)
As editors of this text, Pamela and I have over 40 years of combined experience in service delivery; education; and research in aging, human rights, disability, and social services. Beginning in 2013, we collaborated on a chapter, Aging and Mistreatment: Victimization of Older Adults in the United States, and as part of that chapter, we wrote about LGBT elders. Afterward, we discussed the lack of focus and collaboration across disciplines in addressing LGBT elders. Although discipline-specific books have been published about LGBT populations, aging, health care, and human and social service, we decided that the time had come for a comprehensive text that addressed the challenges faced by LGBT elders. Our goal for this book is to discuss both LGBT elders who are from groups for which research was conducted often and groups rarely included in mainstream research (e.g., racial and ethnic groups, persons living in rural and remote areas, veterans, [ex]-offender populations, immigrants, and persons with disabilities). In addition, we decided to cover issues that impact LGBT persons individually and collectively. Our 36 chapters cover the following topics pertaining to LGBT elders: theories and constructs, the nexus of sexual minority status and aging, family relationships, deconstruction of “isms,” African American and Blacks, American Indians, Asian and Pacific Islanders, Europeans, Hispanics, veterans, [ex]-offenders, immigrants, transgendered persons, bisexual persons, mistreatment and victimization, bullying, healthcare reform and healthcare practices, residents of long-term care facilities, end-of-life issues, mental health, substance abuse, the impending US Supreme Court ruling on same-sex marriage, ethics and ethical standards, law enforcement and public safety, religious and faith communities, workplace issues, counseling, socialization and recreation, advocacy, disability, and trends and future directions. Our comprehensive handbook recognizes the intersection of identities because individuals do not exist or live their lives in separate compartments.
An Interdisciplinary Approach to Principles, Practices, and Policies